2012
DOI: 10.1084/jem.20120831
|View full text |Cite
|
Sign up to set email alerts
|

Congenital B cell lymphocytosis explained by novel germline CARD11 mutations

Abstract: Germline mutations in CARD11 that result in constitutive NF-κB activation and selective B cell expansion underlie congenital B cell lymphocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
233
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(259 citation statements)
references
References 38 publications
19
233
5
1
Order By: Relevance
“…31,32 This spontaneous complex formation was correlated previously with constitutive, receptorindependent, NF-kB activation. Here, we analyzed the subcellular distribution of DDK-CARD11 proteins by immunofluorescence after transfection into HEK 293 cells.…”
Section: Mutant Card11 Assembles In Cytoplasmic Aggregates Associatedsupporting
confidence: 60%
“…31,32 This spontaneous complex formation was correlated previously with constitutive, receptorindependent, NF-kB activation. Here, we analyzed the subcellular distribution of DDK-CARD11 proteins by immunofluorescence after transfection into HEK 293 cells.…”
Section: Mutant Card11 Assembles In Cytoplasmic Aggregates Associatedsupporting
confidence: 60%
“…Interestingly, it has been recently demonstrated that germline gain of function mutations of CARD11, involved in NF-kB activation in both B and T cells, could induce lymphoproliferation restricted to B cells. 22 Alternatively, the genetic events allowing clonal B cells to escape may occur within the B cells themselves. Autoimmune B cells subjected to perpetual stimulation are more sensitive to the presence of additional mutations leading to clonal selection.…”
Section: Discussionmentioning
confidence: 99%
“…Some gain-of-function (GOF) CARD11 alleles have been associated with B-cell lymphoproliferation, 29,30 and a GOF effect could in principle explain the lymphoproliferative features of OS in P1. To study the impact of the second-site mutation on the cellular behavior of lymphocytes, we made use of a murine model that has previously been established to evaluate human CARD11 GOF mutations.…”
Section: The Card11 Pcys150leu Variant Does Not Confer Gain-offunctimentioning
confidence: 99%
“…The functional reversion resulted in reconstitution of protein expression with partial reconstitution of NF-kB phosphorylation and subsequent transcriptional activity. Mutations in the coiledcoil domain of CARD11 have been associated with congenital B-cell lymphoproliferation 29 and B-cell lymphoma. 30 However, we documented that the p.Cys150Leu mutation did not elicit increased spontaneous or induced NF-kB signaling, and our murine experiments 25 render it unlikely that it conferred autonomous proliferative activity to patient T cells.…”
mentioning
confidence: 99%